Symbolic Violence among Characters in Selected Eka Kurniawan’s Works - Putri, Christiana Anindya (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
This article explores symbolic violence experienced by men and women in their everydaylives as portrayed in selected Eka Kurniawan’s works: Beauty is a Wound (2016), Man Tiger(2015), and Vengeance is Mine, All Others Pay Cash (2017). In order to identify the symbolicviolence, Pierre Bourdieu’s concept of symbolic violence is applied in this research. Thefinding of this research indicates that symbolic violence experienced by men and women isthe result of patriarchal system which is manifested in culture and tradition. This culture andtradition has power to discipline society and it also induces symbolic violence towardssociety since they are required to follow the patriarchal values or stereotype. The symbolicviolence against men and women in selected Kurniawan’s works are depicted througharranged marriage, marital rape, women’s obligation in domestic domain, and men’s sexualperformance and masculinity.Keywords: patriarchy, symbolic violence, stereotype